2022
DOI: 10.1177/0734242x221101531
|View full text |Cite
|
Sign up to set email alerts
|

Waste audits in healthcare: A systematic review and description of best practices

Abstract: Healthcare generates large amounts of waste, harming both environmental and human health. Waste audits are the standard method for measuring and characterizing waste. This is a systematic review of healthcare waste audits, describing their methods and informing more standardized auditing and reporting. Using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we searched MEDLINE, Embase, Inspec, Scopus and Web of Science Core Collection databases for published studies involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 162 publications
0
8
0
Order By: Relevance
“…The relative percentage of wastes with particular physicochemical characteristics and total quantities produced are site specific. 62 Local reconciliation and planning at the hospital and regional level along with national data reporting are therefore critical for waste minimization and accountability. 63 In many countries, hospitals and clinics are legally responsible for minimizing waste and occupational exposure, segregating waste into proper receptacles, treating potentially infectious waste, and ensuring documentation of waste fractions produced and their proper storage, transportation, and disposal.…”
Section: Surgical Wastementioning
confidence: 99%
See 1 more Smart Citation
“…The relative percentage of wastes with particular physicochemical characteristics and total quantities produced are site specific. 62 Local reconciliation and planning at the hospital and regional level along with national data reporting are therefore critical for waste minimization and accountability. 63 In many countries, hospitals and clinics are legally responsible for minimizing waste and occupational exposure, segregating waste into proper receptacles, treating potentially infectious waste, and ensuring documentation of waste fractions produced and their proper storage, transportation, and disposal.…”
Section: Surgical Wastementioning
confidence: 99%
“…These properties define appropriate methods of decontamination, recycling, and disposal. The relative percentage of wastes with particular physicochemical characteristics and total quantities produced are site specific 62 . Local reconciliation and planning at the hospital and regional level along with national data reporting are therefore critical for waste minimization and accountability 63 …”
Section: Observations: the Surgical And Anesthesia Device Lifecyclementioning
confidence: 99%
“…Waste in critical care has been of the topic of great interest to researchers and practitioners alike [ 17 , 22 – 25 ], with various case studies published showcasing wasteful stocking and disposal practices. For example, Hunfeld et al [ 21 ] reported that individual units used per ICU patient per day to be high as 108 disposable gloves, 57 compresses, 34 liquid medicine (infusion bags), 24 syringes, 23 tubes and connectors, 16 disposable clothing, 14 cups and containers, 11 tablets and capsules, 9 surgical masks, and 8 bed liners.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is an increasing amount of literature on the management of health care waste with a recent review of musculoskeletal literature reporting 49 original articles on the topic, which emphasizes the growing importance of this topic to both surgeons and health care facilities. 2,3 Because hospitals face increasing scrutiny to contain burgeoning health care costs and waste generation, identifying and reducing the sources of extraneous costs and waste is growing increasingly important. 4,5 A large proportion of the cost and waste generated by hospitals originates from operative procedures giving surgeons the opportunity to be important stewards of hospital resources and drivers of cost and waste reduction.…”
Section: Introductionmentioning
confidence: 99%
“…1 There is an increasing amount of literature on the management of health care waste with a recent review of musculoskeletal literature reporting 49 original articles on the topic, which emphasizes the growing importance of this topic to both surgeons and health care facilities. 2,3…”
Section: Introductionmentioning
confidence: 99%